Perlindungan Hukum Terhadap Hak-Hak Keperdataan Anak Dari Perkawinan Campuran Yang Tinggal Di Indonesia Berdasarkan Undang-Undang Nomor 12 Tahun 2006 Tentang Kewarganegaraan - Maria Ulfah; Nahdhah Nahdhah; Norisnaniah Norisnaniah (Jurnal Penegakan Hukum Indonesia, 2022)
There were many cases derived from transnational marriages. For an instance, many Indonesian international students have married their spouses from the country where they are studying. Transnational marriage is prone to future conflicts, especially regarding the status of the children. The civil rights of children from a transnational married couple living in Indonesia are regulated on Act No. 12/2006 on Citizenship (Citizenship Act). This research is pure legal research that is carried out by examining previous literature. From this study, it was found that the status of children born from transnational families according to the Citizenship Act is based on bloodlines following the father. If the father is a foreign citizen, the child will also be a foreign citizen. On contrary,  if the father is an Indonesian citizen, the legal status of the child is also as an Indonesian citizen, from here the role of the mother becomes neglected. Furthermore, Citizenship Act guarantees that the children have the right to determine or choose citizenship after the age of 18 years, the child is required to choose one nationality. Legal protection for children born from transnational marriages is the right to choose their nationality.